Cloud Fault Modeling - Okado Tamashiro, Camila Baleiro; Spolon, Roberta [UNESP]; Lobato, Renata Spolon [UNESP]; Manacero Junior, Aleardo [UNESP]; Cavenaghi, Marcos Antonio; Rocha, A.; Perez, B. E.; Penalvo, F. G.; Miras, M. D.; Goncalves, R. (Ieee, 2020)
In this work, fault modeling for simulators that work in the infrastructure as a service of the cloud computing architecture is presented. Due to the increased demand for online services and solutions, cloud computing has grown exponentially in recent years, as has the storage of your information, its services delivered and offered online. These factors have collaborated so that, increasingly, the services offered are fault-tolerant, whether they are related to software or hardware. For that, it is necessary that the cloud environments, be prepared with techniques for the detection and treatment of failures if they occur. In this way, this work studied the possible flaws in the cloud computing architecture and their respective techniques for detection and treatment in cloud environment simulators. This study was based on the main failures and fault tolerance techniques existing in relevant cloud managers today. Thus concluding that, in order to be successful in fault-tolerant systems, it is necessary to create libraries that allow their detection and their respective treatment.
Keywords: Cloud computing; fault tolerance; modeling